Dampak Kompetensi, Motivasi, dan Disiplin Kerja Terhadap Kinerja Pegawai pada Kantor Kecamatan Mariso - wijaya, indra wijaya; Yulianti, Sintia; Rakhman, Basri (Badan Penelitian dan Pengembangan Daerah Kota Makassar, 2024)
This study explores the impact of competence, motivation, and work discipline on civil servants performance at the Mariso District Office. Using a quantitative approach, data were collected from 47 employees through a survey, with multiple regression analysis used to assess the relationship between the variables. The findings show that motivation and work discipline are significantly correlated with employee performance, with motivation emerging as the most dominant factor. Competence, while important, has a smaller impact compared to the other two variables. These results show that fostering motivation and discipline is key to improving employee performance in public sector organizations. This study contributes to the existing literature by integrating these factors and offers practical implications for human resource management practices in public administration. Future research is recommended to explore the longitudinal impact and role of leadership and organizational culture in shaping performance outcomes.